"Ear of the Lynx" Sign in Hereditary Spastic Paraparesis (HSP) 76. Issue 1 (17th November 2022) - Agarwal, Ayush; Oinam, Rahul; Goel, Vinay; Sharma, Pooja; Faruq, Mohd.; Garg, Ajay; Srivastava, Achal K.
Abstract: Background: Hereditary Spastic Paraparesis ( HSP) are a group of genetically inherited disorders, clinically and genetically heterogenous and characterized by degeneration of corticospinal tracts, manifesting with progressive spasticity and lower limbs weakness. Most HSPs have an autosomal dominant inheritance. "Ear of the Lynx" sign describes the characteristic abnormality in the forceps minor region of the corpus callosum (CC) on MRI brain. These bear a striking resemblance to the ears of a lynx. This finding has previously been described with hereditary spastic paraparesis 11 and 15, both of which are autosomal recessive HSPs. Cases: We describe this finding in two siblings with novel mutations causing HSP76, an extremely rare autosomal recessive HSP (less than 50 cases described worldwide), which has not been reported previously. Conclusion: This sign suggests the presence of pathogenic genetic mutations and is likely indicative of autosomal recessive HSPs.